COMMERCIALIZATION OF INNOVATIVE ACTIVITIES AND ESSENCE OF INNOVATIVE ENTREPRENEURSHIP - Boris М. Getman; Olga А. Nenakhova; Victoria А. Chistova (Advanced Engineering Research)
The conceptual framework of commercialization in the market system is revealed. The essence of the innovation business in the regulation of the commercial innovative activities is analyzed. The main problems of the innovative entrepreneurship are observed.